Development of Parenteral Nutrition–Associated Liver Disease and Other Adverse Effects in Neonates Receiving SMOFlipid or Intralipid. Issue 8 (6th February 2020) - Stramara, Lindsey; Hernandez, Lela; Bloom, Barry T.; Durham, Christopher
Abstract: Background: Intravenous lipid emulsions (ILEs) are a risk factor for parenteral nutrition–associated liver disease (PNALD) in the neonatal population. Current literature supports the use of SMOFlipid (4‐oil ILE), a fish oil–containing lipid emulsion, for the reversal of PNALD. However, there is little information about the use of 4‐oil ILEs for preventing PNALD. The purpose of this study is to examine the safety of a 4‐oil ILE in neonates and its effectiveness in preventing PNALD among neonates compared with Intralipid (a soybean‐oil, SO‐ILE). Methods: This is an observational, cohort, comparative safety study, conducted in a level III neonatal intensive care unit. Participants include neonates who received a 4‐oil ILE in their parenteral nutrition (PN) formula, who were matched with historical data of patients who received an SO‐ILE, in a 1:3 fashion (4‐oil ILE:SO‐ILE). The primary outcome of this study is the presence of PNALD (defined as direct bilirubin > 2 mg/dL) after initiation of PN. Results: A total of 1332 participants (333 4‐oil ILE vs 999 SO‐ILE) were included in the data analysis, and PNALD was found to occur in 1.8% of patients in the 4‐oil ILE group and 3.6% of patients in the SO‐ILE group (Relative risk (RR) 0.5; 95% CI, 0.21–1.18). Conclusion: The decrease in the incidence of PNALD among the 4‐oil ILE group compared with the SO‐ILE group indicates a 4‐oil ILE may have a hepatoprotective effect.